PROBLEMS OF PHYSICAL CULTURE (Intent Research Scientific Journal, 2023)
The content of the article reveals the relationship of physical culture with its general culture. Essence and connections in the general culture of the individual. The basic means of formation of the general culture of the person in the course of employment by physical training and sports are resulted.